Odpowiedź:
g) ( 1 i 5/6 +3/4 ) : 1 i 7/24= ( 1 i 10/12 + 9/12) : 31/24= 1 i 19/12 : 31/24 =
= 2 i 7/12 : 31/24= 31/12 * 24/31( skracamy 31 i 31 przez 31, oraz 12 i 24
przez 12)= 2
h) ( 1 i 1/12 - 2 i 1/8) :5/12= ( 1 i 2/24 - 2 i 3/24 ): 5/12= - 1 i 1/24:5/12=
= - 25/24 * 12/5( skracamy 25 i 5 przez 5, oraz 24 i 12 przez 12)=
= - 5/2 = - 2 i 1/2
i) ( 2 i 2/15 - 3 i 3/10 ) : 1 i 1/6= ( 2 i 4/30 - 3 i 9/30) : 7/6=- 1 i 5/30 :7/6=
-1 i 1/6:7/6= - 7/6 * 6/7 ( skracamy 7 i 7 przez 7, oraz 6 i 6 przez 6)= -1
Szczegółowe wyjaśnienie: